V. Shinkle correspondence - Shinkle, V.
ALS (1877 October 23; Covington, Ky.) written by Shinkle to President Rutherford B. Hayes recommending C.C. Adams for the office of commissioner of customs.
President of Kenton Insurance Company, Covington, Ky.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, C. C; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Customs administration -- United States; Insurance executives